ULTRASPEC: High-speed spectroscopy with zero readout noise - Dhillon, V; Marsh, T; Copperwheat, C; Bezawada, N; Ives, D; Vick, A; O'Brien, K (2008)
ULTRASPEC is a high-speed, spectroscopic camera based on electron-multiplying CCDs (EMCCDs) and the data acquisition system of ULTRACAM. The camera saw first light in December 2006 on the EFOSC2 spectrograph of the ESO 3.6 m telescope at La Silla. In this paper we describe the motivation behind ULTRASPEC, present an outline of its design and report on its measured performance. The results show that EMCCDs are likely to revolutionise astronomical spectroscopy. © 2008 American Institute of Physics.